DISPARITAS PUTUSAN HAKIM TENTANG DISPENSASI KAWIN PERKARA NOMOR 1484/PDT.P/2020/PA.KAB.MLG DAN PERKARA NOMOR 1172/PDT.P/2020/PA.KAB.MLG (STUDI KASUS DI PENGADILAN AGAMA KABUPATEN MALANG KELAS 1A) (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
This research is used to analyze two problems: first, how disparity of judges decision of marriage dispensation especially in case Number 1484/Pdt.P/2020/PA.Kab.Mlg and case Number 1172/Pdt.P/2020/PA.Kab.Mlg. Second,what is being judge’s basic consideration for fulfill marriage dispensation especially in case Number 1484/Pdt.P/2020/PA.Kab.Mlg. This research is use qualitative approach with make use of interview method and documentation. The result of this research is show that : First, disparity of judge’s decision can happen purely because of the thought and the judge’s decision . Second, judge’s basic consideration for fulfill marriage dispensation is The Law Number 16 Year 2019 about Change of Law Number 1 Year 1974 about Marriage and Law Number 3 Year 2006 about Change of Law Number 7 Year 1989 About religious court. Furthermore, The judge is see the applicant effort for come to religious court, fulfill the requirements that required and marry of his child accordance with the applicable constitution.